Narrative role of vitamin D receptor with osteoporosis and obesity in a sample of Egyptian females: a pilot study - Nayera E. Hassan; Sahar A. El-Masry; Waheba Ahmed Zarouk; Ghada Nour Eldeen; Rehab M. Mosaad; Mahmoud A. S. Afify; Manal M. Aly; Aya Khalil (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Vitamin D receptor (VDR) is known as one of the cellular regulators for several metabolic pathways indicating its pivotal role in the pathological pathway of numerous diseases. Considering the high frequency of osteoporosis and obesity among women, the current study aimed to explore the prospective assembly of the most frequent two VDR loci, single nucleotide polymorphism SNPs rs731236 (TaqI) and rs7975232 (ApaI) with a genetic predisposition to osteoporosis (skeletal) and obesity (chronic non-skeletal disorders), in Egyptian women. This was a cross-sectional study, including 97 Egyptian females (25–65 years), randomly chosen, from all employees and workers of the National Research Centre, Egypt. Anthropometric measurements (weight, height, BMI), dual-energy X-ray absorptiometry (DEXA), and molecular genetic analysis were done. Results The variation of ApaI genotype between the normal and osteoporotic groups denotes a remarkable association of the homozygote ApaI genotype with osteoporosis risk. Among the normal weight group, bone mineral density (BMD) was significantly associated with TaqI VDR gene polymorphism as the presence of the heterozygote genotype was accompanied with higher BMD while the homozygote one was detected with lower BMD. Also, TaqI VDR gene polymorphism was significantly associated with BMI when participants were divided according to the presence of osteoporosis; increased BMI was expressed in the non-osteoporotic women group carrying the homozygote genotype of Taq I VDR gene while the presence of the heterozygote genotype (TaqI) in the osteoporotic group was associated with increased BMI. Conclusions The heterozygote TaqI genotype is protective against the osteoporosis phenotype and accompanied with increased BMI among osteoporotic women, while the homozygote ApaI genotype has a significant association with osteoporosis risk.